Constitutionality Degree of Indonesia Local Regulation in Political Law Perspective - Bambang Sutrisno (Universitas Muhammadiyah Sidoarjo, 2016)
The Politics of Law holds responsibility to give the surety of all regulations, including Local Regulation, for capable of reflecting the collective will of the public as the owner of the highest sovereignty. Politics of law is always working to bring together the ius constituendum and ius constitutum at the encounter between realism and idealism. Local Regulation as subsystems of national law, is expected to serve as a guiding instrument and guard direction for development and continuous improvement of Local Government. Therefore the existence of local regulations holds a strategic role for legal certainty, which is a necessary to create a conducive business climate and stability of the country.